An artificial intelligence–assisted project-based hybrid learning model for enhancing students’ digital literacy competence - Surya Priyambudi; Yulis Setyowati; Alven Safik Ritonga (Universitas PGRI Pontianak, 2025)
The urgency of this study lies in integrating three pedagogical approaches—Project-Based Learning, Hybrid Learning, and Artificial Intelligence—to enhance students’ digital literacy competence, thereby producing a learning model that can be implemented in the ICT Media course and preparing graduates with the digital literacy skills required in the era of Society 5.0. The research questions addressed in this study are as follows: (1) Is the AI-assisted Project-Based Hybrid Learning (PjBHL) model feasible for use in the ICT Media course at Universitas Wijaya Putra? (2) Is the AI-assisted PjBHL model practical to implement in the ICT Media course at Universitas Wijaya Putra? and (3) Does the use of the AI-assisted PjBHL model improve students’ digital literacy competence in the ICT Media course at Universitas Wijaya Putra? The problem-solving approach adopted in this study began with identifying students’ low levels of digital literacy competence based on classroom observations and pretest results. This condition was further analyzed by examining the limitations of the direct instruction learning model in fostering digital literacy skills, highlighting the need to explore the potential of Artificial Intelligence in supporting the PjBHL model. Accordingly, this study aims to determine the feasibility, practicality, and effectiveness of the AI-assisted PjBHL model in enhancing students’ digital literacy competence. To achieve these objectives, a development research design employing the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation—was applied. Based on the five stages of the ADDIE framework, the AI-assisted PjBHL model was found to be feasible, practical, and effective in improving students’ digital literacy competence. The model also received positive responses from students and was evaluated as relevant by experts in learning, ICT, and educational technology. Overall, the average increase in students’ digital literacy competence reached 24.4 points across all indicators.